Results of Second-Look Laparotomy in Advanced Ovarian Cancer: One Single Center Experience - Damak, Tarak (International Scholarly Research Network, 2012)
Objective. The goal of the study was to analyse the results of 85 cases of second-look laparotomy (SLL) and explore the influence of this procedure on survival. Patients and Methods. We reviewed retrospectively 85 cases of SLL collected and treated in our institute between 1994 and 2003. Results. Complete pathologic response (CPR) was 25.8%, microscopic disease (Rmicro) was 38.8%, and macroscopic disease (Rmacro) was 35.4%. In patients with negative SLL results, disease recurrence was diagnosed in 41%. The 3- and 5-year overall survival rates for the entire population were 91% and 87%, respectively. The 3- and 5-year disease-free survivals were, respectively, 76.3% and 58.5% in negative SLL versus 55.7% and 16% in positive SLL. The difference between the group of patients with complete response (76%) and the patients with residual microscopic disease (72%) was not significant. The tumoral residuum after initial surgery was the only prognostic factor influencing significantly the disease-free survival. On Cox regression model analysis, only initial tumoral residuum (P = 0.04) and tumoral residuum after SLL (P = 0.02) were independent prognostic factors for survival. Conclusions. The most important advantage of SLL is the early detection of recurrence and thus the early administration of consolidation treatment resulting in a better prognosis.